2012
DOI: 10.1016/j.jviromet.2012.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of methods for the detection of coliphages in recreational water at two California, United States beaches

Abstract: Methods for detection of two fecal indicator viruses, F+ and somatic coliphages, were evaluated for application to recreational marine water. Marine water samples were collected during the summer of 2007 in Southern California, United States from transects along Avalon Beach (n=186 samples) and Doheny Beach (n=101 samples). Coliphage detection methods included EPA method 1601 - two-step enrichment (ENR), EPA method 1602 - single agar layer (SAL), and variations of ENR. Variations included comparison of two inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In Mexico, viruses are not considered in water quality regulations, although elsewhere, somatic and male F+ specific coliphages have been exploited effectively as potential viral indicators of faecal contamination in a variety of aquatic environments (U.S. EPA ; Jofre et al ). Despite the value of such tests, methods for recovering and detecting coliphages can be influenced by several variables, including the efficiency with which the pathogen can be concentrated from different types and volumes of water sampled (Contreras‐Coll et al ; Rodríguez et al ), raising the necessity to determine the efficiency of these methods for different water environments. Previous studies have shown that double layer assay methods together with very low water volumes (10 ml) were used successfully to enumerate somatic and male F+ specific coliphages in groundwater samples from the YP karst aquifer.…”
Section: Discussionmentioning
confidence: 99%
“…In Mexico, viruses are not considered in water quality regulations, although elsewhere, somatic and male F+ specific coliphages have been exploited effectively as potential viral indicators of faecal contamination in a variety of aquatic environments (U.S. EPA ; Jofre et al ). Despite the value of such tests, methods for recovering and detecting coliphages can be influenced by several variables, including the efficiency with which the pathogen can be concentrated from different types and volumes of water sampled (Contreras‐Coll et al ; Rodríguez et al ), raising the necessity to determine the efficiency of these methods for different water environments. Previous studies have shown that double layer assay methods together with very low water volumes (10 ml) were used successfully to enumerate somatic and male F+ specific coliphages in groundwater samples from the YP karst aquifer.…”
Section: Discussionmentioning
confidence: 99%
“…First, the bacteria were cultured on a Tryptone Soya Agar (TSA) culture medium containing ampicillin and streptomycin antibiotics and incubated at 37 °C overnight. A colony was then taken from the culture medium and inoculation in a Tryptone Soya Broth (TSB) containing the antibiotics above until it reached 0.1–0.5 optical density at 600 nm wavelength at 37 °C (Rodríguez et al ., 2012).…”
Section: Methodsmentioning
confidence: 99%
“…In order to ensure that water sources are not contaminated or polluted, fecal indicator bacteria or viruses, for example coliphages and Bacteriodes fragilis phages are being monitored when the analysis of water samples of public health concern is carried out (Rodríguez et al, 2012). Point source contamination is revealed when there is presence of fecal indicator bacteria or viruses.…”
Section: A11 Backgroundmentioning
confidence: 99%
“…The presence of coliphages has been used for the correlation of fecal contamination and this is particularly advantageous because it serves as a complementary method to bacterial indicators. In particular, the enumeration of coliphages appears to be much simpler (Leclerc et al, 2000;Rodríguez et al, 2012).…”
Section: A11 Backgroundmentioning
confidence: 99%
See 1 more Smart Citation